GISTO-ULTRASTRUCTURAL CHANGES IN THE MUSCLES OF THE ABDOMINAL IN VENTRAL HERNIA AND AFTER PHYSICAL REHABILITATION IN THE POSTOPERATIVE PERIOD AFTER ALLOPLASTY - Melnyk, I.V.; Popel, S.L.; Lapkovskiy, E.Yo.; Vasylyk, T.P. (World of Medicine and Biology, 2021)
The study of histo-ultrastruction changes of different structural components of direct muscle of abdominal of sexually matured rats – males was a research purpose in the remote terms of ventral hernia and subsequent application of the physical loading of middle aerobic power. Light opticaly, electronical microscopical (for the exposure of structural transformations of muscle components) and histochemical (for determination of activity of succinate dehydrogenase after Nahlas – to identify muscular fibres with different phenotypes) methods at 55 sexually matured rats were studied structural track of adaptation of muscle compartmently at prolonged (240 days) ventral hernia and after 15-30 multiple physical loading of middle aerobic power in an ambassador post-operative period at alloplastic. It is shown that above all things, there are the changes of intramuscular network and morfometric changes blood vessels. These information closely correlate with the making progress changes of subcellular components of muscle fibers accountable for power and plastic balance. It is set that fast oxygen-glycolytics muscle fibers and their peripheral nervous vehicle are most sensible to the terms of prolonged ventral hernia. As a result of application of the physical loading of middle aerobic power the reparative regeneration is intensifyed, that substantially abbreviates the terms of renewal of structurally-functional properties of skeletal muscles in the conditions of ventral hernia illness. Thus, at ventral hernia the primary changes touch the sources of blood supply of abdominal muscles, with the secondary paranecrosis processes in muscle fibers and peripheral nervous vehicle with certain morfometric signs.